Global Biogeochemical Cycle of Fluorine. Issue 12 (26th November 2020) - Schlesinger, William H.; Klein, Emily M.; Vengosh, Avner
Abstract: This review provides a synthesis of what is currently known about the natural and anthropogenic fluxes of fluorine on Earth, offering context for an evaluation of the growing environmental impact of human‐induced F mobilization and use. The largest flux of F at the Earth's surface derives from the mobilization of F during chemical (2.2 Tg F/yr (where 1 Tg = 10 12 g) and mechanical (7 Tg F/yr) weathering of rocks. Humans supplement these fluxes by mining fluorospar and apatite ores to make a variety of industrial chemicals and fertilizers, mobilizing 2.9 and 7.6 Tg F/yr, respectively. Other large anthropogenic fluxes derive from the manufacture of bricks (1.8 Tg F/yr) and extraction of groundwater (0.9 to 1.7 Tg F/yr). Rivers deliver 3.6 Tg/yr of dissolved fluoride to the oceans, where the mean residence time of dissolved F in seawater is 500, 000 yr. F is removed from the oceans by the deposition of terrigenous (4.3 Tg F/yr) and authigenic sediments (1.24 Tg F/yr), and approximately 10 Tg F/yr is removed from the surface of the Earth by subduction of the oceanic lithosphere. Humans have increased the flux of F to the atmosphere and in rivers by more than a factor of 2, with the largest impacts stemming from the use of phosphorus fertilizers, the production of brick, and extraction of groundwater. Despite their well‐documented toxicity, perfluoroalkyl substances make only a small contribution to F emitted to the atmosphere and natural waters. Key Point: The movement of F in its global cycle has been substantially impacted by human activities